Is God dead? The Nietzschean phrase about the “death of God” and the vitality of monotheisms in the Modern Age - Uhde, Bernhard (2014)
Currently, the great monotheistic religions –Judaism, Christianity and Islam– may seem anachronic. Judging from their principles and rituals, they appear to belong to the Middle Ages. This seems to be confirmed by a brief consideration of the history of Western science, certainly marked by first philosophy, and by its division into its three periods: ancient, medieval and modern. The One, recognized by Plotinus as the necessary condition of all multiplicity, and which religions identify with God, may be considered the principle of medieval thought. Alongside Descartes, modernity replaced this principle, and by the end of this period Nietzsche claimed that “God is dead! God remains dead! We have killed him!” But, is God dead? If the Modern Age, which started with Nietzsche, has killed God, does it mean that monotheistic religions have also been deprived of life and vitality? Or do they continue to live thanks to a free and self-determined assent to a living God that can be thought in relation to the world and to men and women?